ChemInform Abstract: Thermal Decomposition of Barium Ferrate(VI): Mechanism and Formation of FeIV Intermediate and Nanocrystalline Fe2O3 and Ferrite. Issue 19 (21st April 2016) - Machala, Libor; Sharma, Virender K.; Kuzmann, Ernoe; Homonnay, Zoltan; Filip, Jan; Kralchevska, Radina P.
Abstract: Thermal decomposition of BaFeO4 in static air and nitrogen atmosphere is monitored by thermal analysis, Moessbauer spectroscopy, powder XRD, and electron‐microscopic methods.